Prospective study using archetypes and system dynamics. Issue 2 (22nd August 2019) - Vera, Patricio; Nikulin, Christopher; Lopez-Campos, Monica; Gonzalez Ramirez, Rosa Guadalupe G.
Abstract : Purpose: The purpose of this paper is to propose a combination of forecasting methods that enables a holistic understanding of a future situation, given certain influencing variables by a combination of real data and expert knowledge. Design/methodology/approach: The proposal combines two well-known methods: first, system archetypes that correspond to generic structures, allowing us to handle model management issues, and second, system dynamics that offers technical support on a computational level to assess different scenarios or problem solutions. Findings: The case study considers the situation of the mining industry in Chile and its related variables, including four different scenarios. Based on the proposed methodology, the results indicate that: first, the price of copper is paramount for the industry and its effects are not limited to company profits; second, a long period of downfall in copper prices could halt exploration and development projects. Research limitations/implications: Systemic archetypes are still a subject of research and their application in different fields of knowledge continues to increase to improve this simulation approach. Practical implications: The case study illustrates the combination of a Vester matrix and initial system archetype models that are enriched using the system dynamics approach. Indeed, the case study aims to understand the consequences of different scenarios based on the problem-driven approach provided by Vester. Social implications: The goal of prospective studies of large-scale and complex situations is to model the real situation to obtain solutions that may enhance social welfare. Originality/value: The proposed methodology contributes to the existing literature by integrating techniques such as the Vester matrix, system archetype modelling and system dynamics simulation, all of which were proposed previously in the literature as independent techniques. Abstract : Propósito: Este artículo propone una combinación de métodos de pronósticos que permite una comprensión holística de una situación futura, dadas ciertas variables de influencia mediante una combinación de datos reales y conocimiento de expertos. Diseño/metodología/enfoque: La propuesta combina dos métodos conocidos: (i) arquetipos de sistemas que corresponden a estructuras genéricas, lo que nos permite manejar los modelos, y (ii) la dinámica de sistemas que ofrece soporte técnico a nivel computacional para evaluar diferentes escenarios o soluciones de problemas. Resultados: El caso de estudio considera la situación de la industria minera en Chile y sus variables relacionadas, incluidos cuatro escenarios diferentes. Según la metodología propuesta, los resultados indican que i) el precio del cobre es primordial para la industria y sus efectos no se limitan a las ganancias de la empresa; ii) un largo período de caída en los precios del cobre podría detener los proyectos de exploración y desarrollo. Limitaciones en la investigación/implicaciones: Los arquetipos sistémicos siguen siendo un tema de investigación y su aplicación en diferentes campos del conocimiento continúa aumentando para mejorar este enfoque de simulación. Implicaciones prácticas: El estudio de caso ilustra la combinación de una matriz de Vester y los modelos de arquetipos del sistema inicial que se enriquecen utilizando el enfoque de dinámica de sistemas. De hecho, el caso de estudio apunta a comprender las consecuencias de diferentes escenarios basados en el enfoque orientado a los problemas proporcionado por Vester. Implicaciones sociales: El objetivo de los estudios prospectivos para situaciones de gran escala y complejas es modelar la situación real para obtener soluciones que puedan mejorar el bienestar social. Originalidad/valor: La metodología propuesta contribuye a la literatura existente mediante la integración de técnicas como la matriz de Vester, el modelado de arquetipos del sistema y la simulación de dinámica de sistemas, todo lo cual se propuso anteriormente en la literatura como técnicas independientes.